DAMPAK PERUBAHAN TEMPERATUR WARNA LAMPU FLUORESEN PADA PRODUKTIVITAS MENGGAMBAR ARSITEKTUR MANUAL MAHASISWA DI STUDIO GAMBAR - LEONARDO . (Serat Rupa: Journal of Design, 2016)
All artificial lightings have effects on human daily activities. Psychologically, warm colour temperature gives relaxation feelings and cool colour temperature promotes alertness to most activities. This present study aims to describe the alteration of colour temperature from artificial lighting on manual students drawing productivity in drawing studio within a short period. A semi-experimental approach is conducted in two studios on a par for two days, involving 26 students of sixth semester to draw a set of interior details to finish in five hours each session on the same time. Each studio is installed with fluorescent tube lamps with different colour temperature for each session. The drawing elements comprehensiveness and the drawing quality are examined to assess lighting condition in the studios. Findings show that the alteration of colour temperature from 2700K to 6500K is significantly positive to productivity while mix of 4000K and 6500K to 4000K is not significant. The benefit of this study leads to reference to lighting design criteria for drawing studio in design institute to enable students to work in a prolonged time without eye overburden. Hence the design brings positive output.Â Keywords : artificial lighting; color temperature; drawing; manual drawing;productivity;Â qualification